FINNVERA: Insights on Impact - Peter Zettinig; Johanna Raitis; Stephane Lhuillery (FINNVERA, 2022)
This research report on Finnvera’s impact sets forth to find answers to the following research questions: (1) “How does Finnvera generate impact, and on what?” and (2) “What is Finnvera’s impact?”
The first question is a “formative assessment” of impact, which is an impact assessment approach that is geared toward the development of services using in-depth case studies on (a) major clients of Finnvera, Andritz, Outotec, Valmet, Wärtsilä, Meyer Turku, and Nokia, and (b) on a selection of typical clients from the small- and medium-sized customer base, including Kopar, Nightingale Health, Optomed, Lamor, and Huone International.
The findings reveal that Finnvera’s impact on large firms is extensive; these firms develop “solution business models” that encompass various necessary components (technology and engineering, sourcing and construction, maintenance, service and operations support), but a considerable share of their businesses, practically entirely where Finnvera is involved, is only viable and sufficient for success with Export Credit Agency (ECA) financing mechanisms in place. Thus, most firms like to view Finnvera as an essential and strategic partner in their endeavor for international competitiveness and growth. The report illustrates a wide array of impact dimensions, including: “Finnish content”, which is the economic value and employment directly and indirectly produced in Finland by themselves or through their distributor network; “Finnish interest” dimensions containing wider and also more future-oriented effects on impact, including HQ activities, research and development (R&D) commitments, supplier ecosystems’ development and outlook, regional impact, tax and employment effects, socio-economic and psychological impacts, and science and education impacts; “Finnish credibility and legitimacy”, which is the impact Finnish institutions have on reducing uncertainty and building reassurance within Finnish firms; and “social and environmental impact in the world”, usually brought about by providing best-in-class and state-of-the-art technologies substituting for dated methods with negative social and environmental externalities.
Concerning small- and medium-sized clients of Finnvera, the direct impact, while individually small in volume in comparison to large client counterparts, is very important because most major multinational firms were once small firms with large potential. This is where Finnvera generates a considerable impact on these firms. Through the granting of loan guarantees, as the primary mechanism, these firms are able to establish themselves and pursue major business opportunities internationally. Finnvera is often a necessary lifeline in turbulent times and for turnaround phases, and it provides these firms with a basis to negotiate and construct their equity in order to take these entrepreneurial opportunities in global niche markets to the next level. The impact of Finnvera is critical in that it provides these small firms with credibility and legitimacy abroad, allows them to build leverage and maintain control over their ventures, accesses promising markets for their products and services, and is essential for engaging in highly promising cooperative arrangements with multinational players who open their global markets for their offerings. In summary, Finnvera acts as an enabler for these firms.
The second question has an underlying purpose: a “summative impact assessment” approach (i.e., to evaluate to what extent impact is created). This question has been approached in two different ways. First, we use the collected primary, in-depth data from the cases at hand (which comprehensively assumes a lion’s share of Finnvera’s business) to ask the question of counterfactuals: “what if Finnvera’s services were not available to these firms?” The straightforward answer to this question is that, for both the multinational large- and small-sized enterprises group and medium-sized enterprises group, the impact can be considered high. This means that, in every business in which Finnvera’s services are used (in extant cases), these businesses or important parts of them or companies overall would likely not exist without Finnvera’s services; they are understood to be without alternatives rather than considered to possess “nice to have” features.
Quantifying the “how much impact” question of the summative impact assessment requires a different approach and method. We designed a natural experiment that applies an analysis on secondary data in different databases, encompassing Finnvera’s internal databases, Statistics Finland databases, and Orbis databases. The analysis was conducted to create counterfactuals and comparative analyses with the objective of evaluating the impact between firms benefitting from Finnvera’s mechanisms and their “close counterparts”, which do not utilize possibilities provided by ECAs. The result we obtained is statistically inconclusive for a number of reasons. Aside from the technical issues of not being able to match (due to confidentiality settings) small- and medium-sized enterprises (SME) namely between databases holding different data, the more striking issue is that Finland, as a small economy, has very few companies competing for the same space internationally; if they do, they also utilize Finnvera in similar ways. Thus, this approach to measuring impact quantitatively has not been fruitful. The report discusses the recommendation to develop primary data for such impact assessments.
Overall, this study reveals a large number of insights that are thoroughly understood within both Finnvera and its most important clients, but are considered less thoroughly understood when considering important stakeholders at ministries or when considering the Finnvera-centered public and political debates. The report makes a number of recommendations that may be addressed in order to enhance Finnvera’s services and the resulting impact in the pursuit to enhance Finnish firms’ growth, internationalization, and persistence in international competition both currently and in the future.